2006
DOI: 10.1128/jb.188.7.2493-2501.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Activity of Marinocine, Synthesized by Marinomonas mediterranea , Is Due to Hydrogen Peroxide Generated by Its Lysine Oxidase Activity

Abstract: Marinocine is a broad-spectrum antibacterial protein synthesized by the melanogenic marine bacterium Marinomonas mediterranea. This work describes the basis for the antibacterial activity of marinocine and the identification of the gene coding for this protein. The antibacterial activity is inhibited under anaerobic conditions and by the presence of catalase under aerobic conditions. Marinocine is active only in culture media containing L-lysine. In the presence of this amino acid, marinocine generates hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 42 publications
3
60
0
Order By: Relevance
“…1). Such a mode of action was first discovered for the AlpP homologue LodA produced by M. mediterranea (31). Interestingly, our results show that the substrate lysine is produced endogenously by the biofilm bacteria and consequently allows for AlpP/LodA activity.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…1). Such a mode of action was first discovered for the AlpP homologue LodA produced by M. mediterranea (31). Interestingly, our results show that the substrate lysine is produced endogenously by the biofilm bacteria and consequently allows for AlpP/LodA activity.…”
Section: Discussionsupporting
confidence: 52%
“…Sucrose-and streptomycin-resistant colonies were screened for kanamycin sensitivity, and gene insertion confirmed by PCR with the primers CAUDIR4-CAUREV5 (which gives a 670-bp fragment in wild-type and first recombination mutants maintaining locus NP_419374) and CAUDIR3-CAU-REV5 (which gives a 2.3-kb fragment in WT and a 2.1-kb fragment in CAU-MUR1 as a result of the substitution of locus NP_419374 with the smaller streptomycin resistance marker). Deletion of the C. violaceum alpP/lodA homologue was achieved by using a previously described method (31). Briefly, a 500-bp region of the gene containing the fourth and fifth conserved domains, out of a total of eight in the homologous proteins, was amplified by PCR using the primers CVDIR2nco and CVREV1 (Table 2).…”
mentioning
confidence: 99%
“…So far, all the described LAAOs, except the lysine oxidase of Marinomonas mediterranea (21), are flavoproteins possessing a FAD binding domain (37). It is reported that LAAOs possess another characteristic sequence motif, RxGGR, and this motif is also present in several families of flavoproteins, including achacin and aplysianin A, monoamine oxidase, corticosteroidbinding proteins, and tryptophan 2-monooxygenases (37).…”
Section: Vol 190 2008 So-laao Enables S Oligofermentans To Inhibitmentioning
confidence: 99%
“…LAAOs, which catalyze the oxidative deamination of amino acids to yield ammonia, hydrogen peroxide, and ketoacids with oxygen consumed (9), have been widely detected in snake and insect venoms (1,30) and in some fungi, algae, and bacteria (17,25,38). According to the substrate spectra, LAAOs can be divided into two categories, one with a broad spectrum of substrates, like the LAAO of Rhodococcus opacus DSM 43250, which catalyzes not only almost all the 20 L-amino acids but also some derivatives (9), and another with a restricted substrate spectrum, like lysine oxidase of Marinomonas mediterranea, which uses lysine exclusively (21). However, SO-LAAO of S. oligofermentans in this study can represent a novel amino acid oxidase by showing detectable activity against only seven L-amino acids (Table 1).…”
Section: Vol 190 2008 So-laao Enables S Oligofermentans To Inhibitmentioning
confidence: 99%
“…It synthesizes an antimicrobial protein that was initially named marinocine and was later named LodA (24,25). LodA is a novel enzyme (EC 1.4.3.20) very specific for L-Lys that catalyzes the reaction L-lysine ϩ O 2 ϩ H 2 O32-aminoadipate 6-semialdehyde ϩ NH 3 ϩ H 2 O 2 .…”
mentioning
confidence: 99%